Diversity of fleas (Siphonaptera) on small mammals within a subalpine ecosystem in the Nevado de Toluca Protected Area, State of Mexico - Zarza, Heliot; Esteban, Mayra; Acosta, Roxana (Zootaxa, 2025)
In Mexico, few studies on the species of fleas associated with rodents in high mountain areas have been conducted, even though these mammals are mainly associated with these ectoparasites to a large extent, and it is a group of species that have a wide distribution and great diversity. The present study determined the diversity of ectoparasites (fleas) in rodents from a subalpine grassland within the Nevado de Toluca Flora and Fauna Protection Area, State of Mexico. Rodent sampling was carried out during the dry season (March and April) and rainy season (August and November) of 2017, at an elevation of 4,050 m above sea level. A total of 147 Sherman traps were set during three consecutive nights across both seasons. Fleas were collected from rodent hair and placed in 70% ethanol in separate vials for each specimen. A total of 217 rodents of three different species were captured: Reithrodontomys megalotis, Peromyscus melanotis, and Microtus mexicanus. From the last two species a total of 117 Siphonaptera from three families, five genera (Hystrichopsylla, Ctenophthalmus, Plusaetis, Strepsylla, Rhadinopsylla), and seven species were obtained. Plusaetis sibynus was the most abundant species and the one that showed the highest prevalence in P. melanotis, the most abundant rodent. Of the flea species found, Ctenophthalmus tecpin and Strepylla villai were new records for the State of Mexico, and three species of the genus Plusaetis had not previously been reported for the Nevado de Toluca area.